High-resolution Spectra of Supernova Remnants in M83 - P. Frank Winkler; Knox S. Long; William P. Blair; Sean D. Points (The Astrophysical Journal, 2023)
In order to better characterize the rich supernova remnant (SNR) population of M83 (NGC 5236), we have obtained high-resolution (∼85 km s ^−1 ) spectra of 119 of the SNRs and SNR candidates in M83 with Gemini/GMOS, as well as new spectra of the young SNRs B12-174a and SN 1957D. Most of the SNRs and SNR candidates have [S ii ]:H α ratios that exceed 0.4. Combining these results with earlier studies we have carried out with MUSE and at lower spectroscopic resolution with GMOS, we have confirmed a total of 238 emission nebulae to be SNRs on the basis of their [S ii ]:H α ratios, about half of which have emission lines that show velocity broadening greater than 100 km s ^−1 , providing a kinematic confirmation that they are SNRs and not H ii regions. Looking at the entire sample, we find a strong correlation between velocity widths and the line ratios of [O i ] λ 6300:H α , [N ii ] λ 6584:H α , and [S ii ] λλ 6716, 6731:H α . The density-sensitive [S ii ] λ 6716: λ 6731 line ratio is strongly correlated with SNR diameter, but not with the velocity width. We discuss these results in the context of previously published shock models.